Southern view of the Shikhara of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Undeshwar Temple is supported by a tall vedibandha (basal mouldings), intricately carved and featuring multiple moldings. The jangha (wall) of the garbhagriha (sanctum sanctorum) has bhadra (central offset) on each of its three sides. The space between these bhadras is occupied by projected stambhas (buttresses). Carved with depictions of deities, these bhadras enhance the temple's aesthetic. The shikhara (superstructure) of the garbhagriha follows the Bhumija architectural style.